Current Issues of Economic Support for Youth Policy in The Field of Leisure Activities in The Eu Countries - Ryzhikh , L.V. (Journal of Ecohumanism, 2024)
Subject. The subject of the study is the mechanism of economic support for youth policy in the field of leisure activities in the EU countries. Goal. The purpose of the study is to identify areas for improving the mechanism of economic support for youth policy in the field of leisure activities in the EU countries. Methodology. Within the framework of this research, methods such as abstraction, comparison, analysis, analogy, observation, generalization and synthesis are used. The results of the study. Within the framework of this study, a refined definition of the category "youth policy" is formulated, the functions of leisure activities and the results of their implementation, as well as the mechanism of their education, are highlighted. A new algorithm for evaluating projects for the development of youth leisure activities has been developed, aimed at stimulating the development of youth policy in less developed EU countries. A mechanism has been developed for organizing and conducting integrated events in the field of youth leisure activities in the EU countries with the involvement of business. The results obtained can become the basis for further scientific research, as well as the development of programs for the development of youth policy in the EU countries. Conclusions. Leisure activities of young people form the potential for the development of society, contribute to the versatile development of personality and integration into society. It is important for obtaining energy and strength for work, as well as for the spiritual, moral and cultural development of the individual. Youth is a key element of the development of society, and the effectiveness of the organization of its leisure activities affects the socio-economic development of the country. To ensure social progress, it is necessary to guarantee equal opportunities for the development of leisure activities of young people in all EU countries. This will contribute to a more effective integration of young people into society, contribute to their spiritual and cultural development. The organization of leisure activities for young people plays a key role in the socio-economic development of the country, since this social group is an important factor in the progress of society. To achieve this goal, it is necessary to develop centralized support mechanisms in less developed EU countries. It is necessary to introduce a new system for evaluating projects in the field of youth leisure activities in order to improve the economic provision of youth policy. Also, an important direction may be the holding of integrated events with the participation of businesses in all EU countries. The funds raised by these measures will be used to develop the leisure sector of young people in countries where business is at a low level of development. The developed proposals will contribute to the socio-economic development of the EU member states.